Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Financial Performance Pemerintah Daerah pada Kawasan Strategis Nasional Gerbangkertosusila - Ramanda Putra, Fitrah Desnata; Muslimin, Muslimin (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
To achieve optimal fiscal decentralization, each district/city must be able to manage its resources in an successful and proficient way. This could be accomplished through local autonomy, over fragmentation. The purpose of this study is to analyze the impact referring to local native income, variables and central government transfer fund variables on the financial execution of the Rule / City Government of the Gerbangkertosila Area of East Java. Regarding the research written by the author, the area used is a report on the implementation of the 2017-2021 city budget for the national strategic area of Gerbangkertosusila, which uses quantitative methods and emphasizes variables of local original income, central government transfer funds and financial performance. The tools used by the authors in this study were processed using SPSS 26 software. The selection of data analysis methods for hypothesis testers from existing variables is using multiple linear regression analysis methods. From various tests conducted by the author, the research results are concluded as follows: (1) Regional Original Revenue has a positive effect on financial performance, meaning that increasing regional original income means also increasing the financial performance of the local government gatekertosila, (2) the balance of funds has a negative effect on financial performance capabilities. In other words, the increase in central government transfer funds will reduce the financial performance of the Regional Government of the Gerbangkertosusila Area. Keywords: Original Local Government Revenue, Balancing Fund, Financial Results